2002
DOI: 10.1021/ol025649i
|View full text |Cite
|
Sign up to set email alerts
|

Reversing the Stereoselectivity of the Intermolecular Pauson−Khand Reaction:  Formation of endo-Fused Norbornadiene Adducts

Abstract: [reaction: see text] An unprecedented endo-selective and regioselective intermolecular Pauson-Khand reaction takes place when heterobimetallic (Mo-Co) complexes derived from N-(2-alkynoyl)oxazolidinones or sultams are heated in the presence of norbornadiene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…1. The structural features of the oxazolidin-2-one ring are comparable with those of similar compounds (Rios et al, 2002;Eknoian et al, 1998). The ring has an envelope conformation, with atom C4 deviating by 0.416 (6) A Ê from the plane de®ned by the other four atoms (N3/C2/O1/C5).…”
Section: Commentmentioning
confidence: 62%
“…1. The structural features of the oxazolidin-2-one ring are comparable with those of similar compounds (Rios et al, 2002;Eknoian et al, 1998). The ring has an envelope conformation, with atom C4 deviating by 0.416 (6) A Ê from the plane de®ned by the other four atoms (N3/C2/O1/C5).…”
Section: Commentmentioning
confidence: 62%
“…The corresponding (Co-W) complex 6 exhibits a similar behaviour [9]. The use of chiral oxazolidinones results in the formation of diastereomeric pairs of heterobimetallic complexes, and the Pauson-Khand reaction of each diastereomer preferentially affords a different diastereomer of the endo adduct [7,9]. This suggests that the chirality of the tetrahedral C 2 CoMo (or W) core controls the stereoselectivity of the Pauson-Khand cyclization; moreover, by removal of the chiral oxazolidinone moiety, enantiomerically enriched adducts could be obtained.…”
Section: Introductionmentioning
confidence: 97%
“…By using menthyl propargyl ether as the starting alkyne, this replacement led to a pair of diastereomeric complexes that after chromatographic separation could be used as starting materials for stereocontrolled Pauson-Khand reactions, following a strategy previously developed by Chung et al [6] with phosphite-substituted dicobalt alkyne complexes. Recently, we have found that the introduction of a (cyclopentadienyl)molybdenum(dicarbonyl) moiety can change drastically the reactivity of alkyne dinuclear complexes [7]. Thus, while the standard Pauson-Khand reaction of norbornadiene with the dicobalt(hexacarbonyl) complex of N-(2-butynoyl)-4,4-dimethyl-1,3-oxazolidin-2-one (1) leads to a mixture of the regioisomeric adducts 2 and 3 with the usual exo stereochemistry [8], the heterobimetallic (Co-Mo) complex 4 affords as a major product an endo-fused adduct 5 with complete regioselectivity (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Several examples have appeared in the literature and include methylenecyclohexanes (20), methylenecyclopropanes (21) and methylenepyranes (22) [42,43]. Cyclopropyl tethered methylenecyclopropanes can give the expected PK products or rearranged hydroindenones in which neither of the two carbon atoms of the alkyne form part of the cyclopentenone ring in the final product [42].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the stoichiometric reaction has been performed with Zr, Ni, Fe, Ti, W and Mo derivatives. In addition, heterobimetallic Co -W and Co -Mo complexes (1), are suitable precursors for the PKR and impart a high degree of selectivity in the process giving exclusively endo adducts 2 (Scheme 2) [19,20].…”
Section: Scheme 1 the Pkr: An Inter-or Intramolecular [2 + 2 + 1] Cycmentioning
confidence: 99%